Self-Reported Anxiety and Depression in a Monocentric Cohort of Patients With Systemic Lupus Erythematosus: Analysis of Prevalence, Main Determinants, and Impact on Quality of Life - Elefante, Elena; Tani, Chiara; Stagnaro, Chiara; Signorini, Viola; Lenzi, Beatrice; Zucchi, Dina; Trentin, Francesca; Carli, Linda; Ferro, Francesco; Mosca, Marta (Frontiers in Medicine, 2022)
Aims of the study: to analyze the prevalence of self-reported anxiety and depression in a monocentric cohort of patients with Systemic Lupus Erythematosus (SLE); to study the main determinants and the impact on quality of life (QoL). Methods: a cross-sectional observational study including adult outpatients with SLE. Demographic and clinical data were analyzed: indices of disease activity (SELENA-SLEDAI); damage (SLICC-DI); comorbidities and concomitant therapies. The definitions for remission (DORIS) and "Lupus Low Disease Activity" (LLDAS) were applied. At enrollment, each patient completed the following questionnaires: SF-36, FACIT-Fatigue, Lupus Impact Tracker (LIT), Systemic Lupus Activity Questionnaire (SLAQ) and the Hospital Anxiety and Depression Scale (HADS) in order to self-assess anxiety and depression symptoms. The Student T-test and Chi2 tests were conducted for univariate analysis. The Spearman test was used for linear correlation between continuous data. Multivariate analysis was performed by multiple linear and logistic regression. Results: 154 consecutive patients with SLE were enrolled, the majority female and Caucasian with a mean age= 43.313.7 years. 79.9% were in LLDAS or remission. 36.4% had a SDI>1. 13.7% of patients had concomitant fibromyalgia. 37.4% had symptoms indicating anxiety and 25% of depression according to the HADS questionnaire. In the multivariate analysis, patients with active disease were significantly more anxious and depressed (p< 0.01) compared to patients in LLDAS or remission. Fibromyalgia and older age were independently associated with anxiety and depression, respectively (p< 0.05). Active skin involvement was significantly linked to depression (p< 0.05). Higher scores on the HADS questionnaire (higher levels of anxiety and depression) were found to be significantly linked to patients' perception of higher disease activity and worse quality of life, irrespective of disease activity, age and fibromyalgia. Conclusions: symptoms of anxiety and depression are frequent in SLE patients, including outpatients with mild/moderate disease. Such symptoms have a significant negative impact on QoL and perception of disease activity, regardless of other factors. Moreover, disease activity, advanced age and fibromyalgia appear to be significantly linked to mood disorders. Assessing symptoms of the anxious-depressive spectrum in patients with SLE could lead to improvement in patients’ perception of health status and quality of life.